APPLICATION OF CLASSICAL INSTRUMENTAL MUSIC THERAPY IN REDUCING PAIN AMONG CHRONIC KIDNEY DISEASE (CKD) PATIENTS: A CASE STUDY - Intan Mega Pratiwi; Alfi Ari Fakhrur Rizal; Taharuddin Taharudin; Annaas Budi Setyawan (Cendekia Medika: Jurnal Stikes Al-Ma`arif Baturaja, 2026)
Pain is a common clinical problem experienced by patients with Chronic Kidney Disease (CKD), particularly critically ill patients with decreased consciousness in the Intensive Care Unit (ICU). Inadequate pain management may increase physiological stress responses and affect hemodynamic stability. Therefore, safe non-pharmacological nursing interventions are needed, one of which is classical instrumental music therapy. This study aimed to describe the implementation of classical instrumental music therapy and the clinical responses observed in a CKD patient with decreased consciousness in the ICU. This study used a descriptive nursing case study design conducted in one patient with advanced-stage CKD who received structured classical instrumental music therapy for four consecutive days. Pain assessment was performed before and after each intervention using the Critical Care Pain Observation Tool (CPOT), along with monitoring of hemodynamic parameters. The intervention was administered for 20–30 minutes once daily using slow-tempo instrumental classical music (60–80 bpm) without lyrics. The results showed a gradual decrease in pain scores, with CPOT scores declining from 5 on the first day to 2 on the fourth day. This was accompanied by reductions in blood pressure (170/100 to 135/85 mmHg), heart rate (125 to 88 beats/minute), respiratory rate (25 to 16 breaths/minute), and Mean Arterial Pressure (MAP) (123 to 102 mmHg). Oxygen saturation remained stable at 100%, while body temperature showed minimal variation. In this case, classical instrumental music therapy was associated with decreased pain scores and changes in physiological responses. This intervention may be considered a complementary nursing approach for pain management in critically ill CKD patients in the ICU.